Feasibility and Safety of Physical Exercise to Preserve Bone Health in Men With Prostate Cancer Receiving Androgen Deprivation Therapy: A Systematic Review. Issue 3 (23rd December 2021) - Cagliari, Maribel; Bressi, Barbara; Bassi, Maria Chiara; Fugazzaro, Stefania; Prati, Giuseppe; Iotti, Cinzia; Costi, Stefania
Abstract: Objective: Men with prostate cancer (PCa) receiving androgen deprivation therapy (ADT) experience the loss of bone mineral density (BMD) and lean body mass, which can increase their risk of falls and fractures. Physical exercise programs with appropriate components and dosage are suggested to preserve BMD and muscle strength, thereby potentially reducing accidental falls and fractures and associated morbidity and mortality. These benefits can be obtained if exercise programs are feasible and safe and if patient adherence is adequate. This systematic review investigates the feasibility and safety of exercise programs aimed at preventing the risk of accidental falls and fractures and BMD loss in men with PCa undergoing ADT. Methods: MEDLINE, Embase, CINAHL, and the Cochrane Library were searched from database inception to June 7, 2021. Randomized controlled trials were included when they analyzed the feasibility and safety of experimental exercise programs targeting bone health in men with PCa receiving ADT. Two reviewers independently selected the studies, assessed their methodological quality, and extracted the data. Exercise feasibility was measured through recruitment, retention, and adherence rates. Exercise safety was measured through the number, type, and severity of adverse events. Furthermore, the components, setting, intensity, frequency, and duration of exercise programs were extracted. Results: Ten studies were included, with a total of 633 participants. Exercise consisted of a combination of aerobic, resistance, and impact-loading exercise or football training. Exercise is feasible in men with PCa undergoing ADT, although football training should be prescribed with caution for safety reasons. Conclusion: Multicomponent exercise programs targeting bone health seem feasible and safe in this population; however, adverse events should be systematically documented according to current guidelines. Impact: The study shows that men with PCa receiving ADT can safely perform exercise programs to preserve bone health and supports that those programs should become part of lifestyle habits. Lay Summary: Men with PCa who are receiving ADT can safely perform exercise programs to preserve bone health and should make exercise an important part of their lifestyle.